Накатывание резьб, червяков, шлицев и зубьев - Лапин В. В. Владимир Викторович; Писаревский М. И. Моисей Исаакович; Самсонов В. В. Владимир Викторович; Сизов Ю. И. Юрий Иванович (Ленинград, Машиностроение, 1986)
Авт. указаны перед вып. дан.